2011
DOI: 10.1615/critrevbiomedeng.v39.i5.40
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signaling in the Microcirculation

Abstract: Several apparent paradoxes are evident when one compares mathematical predictions from models of nitric oxide (NO) diffusion and convection in vasculature structures with experimental measurements of NO (or related metabolites) in animal and human studies. Values for NO predicted from mathematical models are generally much lower than in vivo NO values reported in the literature for experiments, specifically with NO microelectrodes positioned at perivascular locations next to different sizes of blood vessels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 236 publications
(279 reference statements)
1
26
0
1
Order By: Relevance
“…Its major physiological functions include dilating vascular smooth muscle, and inhibiting the aggregation of platelets, platelet and leukocyte adhesion and hyperplasia of the vascular smooth muscle (18,19). Hormones can damage vascular endothelial cells in which NO is produced and inhibit the activity of NO synthase (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…Its major physiological functions include dilating vascular smooth muscle, and inhibiting the aggregation of platelets, platelet and leukocyte adhesion and hyperplasia of the vascular smooth muscle (18,19). Hormones can damage vascular endothelial cells in which NO is produced and inhibit the activity of NO synthase (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…While NO quickly diffuses away from eNOS to reach its targets, there appears to be a system in place to regulate the amount of NO capable of traversing the cell membrane as models of unregulated diffusion do not consistently account for the biochemistry of eNOS-dependent signaling [6, 94]. Work by Straub et al showed that hemoglobin α (Hbα) is present at the MEJ and acts to regulate NO passage.…”
Section: The Myoendothelial Junction and No Signalingmentioning
confidence: 99%
“…NO is a short-lived molecule with diverse biological functions. Thought to evolutionarily precede both the presence of oxygen in the atmosphere and the development of heme-containing proteins, NO is a ubiquitous signaling molecule [6]. It plays an important role in neurotransmission [7, 8], regulation of vascular tone and vasodilation [9, 10], and regulation of both gene transcription [11, 12] and mRNA translation [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any potential time delay between the onset of CFL variation and NO/O 2 responses was not considered. Buerk et al (2011) previously reported that acute changes in the WSS over short time periods may not be sufficient to induce changes in the eNOS expression. In a separate study, Andrews et al (2010) performed measurements of the shear stressinduced NO production from endothelial cells in a flow chamber.…”
Section: Potential Limitations Of the Current Studymentioning
confidence: 99%